Eye tracking and usability in digital informational environments: theoretical review and evaluation procedure proposal - Roa-Martinez, Sandra Milena; Vidotti, Silvana Aparecida Borsetti Gregorio (Pontificia Universidade Catolica Campinas, 2020)
Defining eye tracking technology as a method of data collection originated by the registration of people's visual tracking, this work's objective is to guide the conceptual and methodological development of future research that intends to use this technology for the evaluation of usability in informational digital environments. For this work's development, we used a descriptive and prospective methodological approach, based on a bibliographic survey, literature analysis, and previous work experiences. As a result, we obtained a set of steps that constitute a proposal of procedure for the evaluation of usability aspects of the eye tracking technology. It is worth noticing that there is a broad panorama and configurations that can be used to evaluate usability within eye tracking. The procedure proposed aims to guide future researchers and projects in these issues, in addition to presenting a consolidated metrics with a meaning in terms of usability aspects' evaluation. To conclude, among the main usability aspects measured during the evaluation by eye tracking metrics are: efficiency in the search, interface and visibility, and that the proposed procedure, besides providing guidance, guarantees that the objectives proposed in this type of research are clearly formulated and fulfilled, as are the validity of their results.
Keywords: Evaluation procedure; Eye tracking; Usability